Determination the time of ovarian activity based on progesterone level in Shami goats during the early breeding season (Damascus University Journal of agriculture sciences, 2021)
The aim of this study was to determine the time of ovarian activity based on progesterone level in Shami goats during the early breeding season. Daily prefeeding- blood samples for 46 days were collected from ten multiparous- non pregnant Shami does (Aug. 11 to Sep. 26, 2015)  by jugular venipuncture and centrifuged at 3000 rpm for 20 min. Plasma was harvested and stored at -20°C until assayed for progesterone using (RIA) radioimmunoassay. The data were statistically analyzed using PROC GLIMMIX in the SAS software package (SAS ® 9.2; 2008). Differences in least square means for progesterone levels were tested using Tukey test. The results indicated that only 20% of Shami goat does showed cyclicity based on progesterone level during the study period, and there were significant differences in the least square means of progesterone concentration between cycling and non-cycling does (1 to 4.5 vs. 0.3 ng/ ml). It may be concluded that progesterone concentration could be an accurate parameter to determine the reproductive status of Shami goats and choosing the most efficient does during the early breeding season.
Keywords: Shami goats; progesterone; Breeding Season